2023
DOI: 10.3390/nu15184016
|View full text |Cite
|
Sign up to set email alerts
|

Chlorogenic Acids, Acting via Calcineurin, Are the Main Compounds in Centella asiatica Extracts That Mediate Resilience to Chronic Stress in Drosophila melanogaster

Helen Holvoet,
Dani M. Long,
Liping Yang
et al.

Abstract: Common symptoms of depressive disorders include anhedonia, sleep problems, and reduced physical activity. Drugs used to treat depression mostly aim to increase serotonin signaling but these can have unwanted side effects. Depression has also been treated by traditional medicine using plants like Centella asiatica (CA) and this has been found to be well tolerated. However, very few controlled studies have addressed CA’s protective role in depression, nor have the active compounds or mechanisms that mediate this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 63 publications
2
7
0
Order By: Relevance
“…First, we tested mixes of CQAs and TTs containing the compounds in concentrations equivalent to CAW (10 mg/mL). We previously showed that the levels of these compounds in CAW are not affected by the preparation of the food and are stable for the 7 days the flies are kept on a food vial ( Holvoet et al, 2023a ). The compounds and compound mixes were prepared in ethanol as 10x stock solutions and therefore the control flies also obtained 10% ethanol in yeast paste.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…First, we tested mixes of CQAs and TTs containing the compounds in concentrations equivalent to CAW (10 mg/mL). We previously showed that the levels of these compounds in CAW are not affected by the preparation of the food and are stable for the 7 days the flies are kept on a food vial ( Holvoet et al, 2023a ). The compounds and compound mixes were prepared in ethanol as 10x stock solutions and therefore the control flies also obtained 10% ethanol in yeast paste.…”
Section: Resultsmentioning
confidence: 99%
“…The preparation of the CA water extract used in this study (BEN-CAW-7) has been previously described in detail ( Holvoet et al, 2023a ; Yang et al, 2023a ). BEN-CA-6 plant material (4 kg) was extracted by boiling in deionized water (50 L) for 90 min.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations